2017
DOI: 10.1038/ng.3912
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–covariate interaction effects and the heritability of adult body mass index

Abstract: Obesity is a worldwide epidemic, with major health and economic costs. Here we estimate heritability for body mass index (BMI) in 172,000 sibling pairs and 150,832 unrelated individuals and explore the contribution of genotype-covariate interaction effects at common SNP loci. We find evidence for genotype-age interaction (likelihood ratio test (LRT) = 73.58, degrees of freedom (df) = 1, P = 4.83 × 10), which contributed 8.1% (1.4% s.e.) to BMI variation. Across eight self-reported lifestyle factors, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
159
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(191 citation statements)
references
References 53 publications
13
159
3
Order By: Relevance
“…The increasing need for large, well‐characterized cohorts of healthy individuals for modern biomedical research, such as genomics or phenomics studies, typically including tens or even hundreds of thousands of subjects, has posed the possibility of using blood services as an option for collecting samples and related data. The possibility to recontact blood donors for repeated sampling or asking for additional data has further increased interest in collecting large biobanks from blood donors.…”
mentioning
confidence: 99%
“…The increasing need for large, well‐characterized cohorts of healthy individuals for modern biomedical research, such as genomics or phenomics studies, typically including tens or even hundreds of thousands of subjects, has posed the possibility of using blood services as an option for collecting samples and related data. The possibility to recontact blood donors for repeated sampling or asking for additional data has further increased interest in collecting large biobanks from blood donors.…”
mentioning
confidence: 99%
“…Robinson et al 6 have previously attempted to quantify the contribution of GxE interactions to the heritability of BMI in a study performed on imputed SNPs from the interim UK Biobank release. Using the GCI-GREML model implemented in GCTA 43 and eight environmental variables that included measures of smoking, hours of TV watched and alcohol frequency, Robinson et al 6 reported that only smoking had significant GxE heritability (4.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross-sectional studies have reported GxE interactions between a linear predictor formed from BMI-associated SNPs and alcohol intake frequency 32 , Townsend Index 32 , physical activity measures 5,32,33 and time watching TV 32,33 , all of which are upweighted in the LEMMA lifestyle score. An alternative approach from Robinson et al 6 binned samples according to their environmental exposure (eg. age) and tested for significant differences in SNP heritability using a likelihood ratio test.…”
Section: Gxe Interaction Analysis In the Uk Biobankmentioning
confidence: 99%
“…Most traits and common diseases in humans are complex because they are influenced by many genetic variants as well as environmental factors 1,2 . Genome-wide association studies (GWASs) have discovered >70,000 genetic variants associated with human complex traits and diseases 3,4 .…”
Section: Introductionmentioning
confidence: 99%